Effects of ALK-5 inhibitor and transforming growth factor-Beta1 in the differentiation of stem cells from human exfoliated deciduous teeth (SHED) into epithelial-like cells - Azmi, Nur Izyan (2018)
Stem cells from human exfoliated deciduous teeth (SHED) are capable to divide, differentiate and mature to the specific types of cells as well as to replenish themselves to regenerate other living cells. Previous study has showed that SHEDs could differentiate into epithelial-like cells. Yet, the effects of Transforming Growth Factor-Beta1 (TGF-β1) or activin like kinase 5 (ALK-5) inhibitor on SHEDs remain unexplored. Thus, the present study was aimed to investigate the effects of TGF-β1 and ALK-5 inhibitor on SHEDs cultured in Keratinocyte Growth Medium (KGM) on its potential to differentiate into epithelial-like cells employing MTT [(3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide)] and alamar blue assays, cell morphology analysis, Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) technique and flow cytometry. A serial dilution of TGF-β1 (0.3125, 0.625, 1.25, 2.5, 5.0, 10.0, 20.0, 40.0, 80.0, and 160.0 ng/ml) and ALK-5 inhibitor (0.156, 0.3125, 0.625, 1.25, 2.5, 5.0, 10.0, 20.0, 40.0, 80.0, and 160.0 μM) concentration was carried out to determine the cell cytotoxicity for each treatment using MTT assay for 72 hours. Afterwards, the three selected concentrations for TGF-β1 (0.3125, 0.625, and 1.25 ng/ml) and ALK-5 inhibitor (0.156, 0.3125, and 0.625 μM) were analysed using alamar blue assay on day 1, 3, 5, 7, and 10 and was done in alpha Minimum Essential Medium (α-MEM) to determine the population doubling time (PDT). The study wasfurther investigated with observation of the cell morphological changes on SHED cultured in KGM only, and with selected concentration of TGF-β1 or ALK-5 inhibitor on day 1, 3, 7, 14, and 21. RNA isolation of SHED culture in three different conditions were harvested at day 1, 3, 7, 14, and 21. Then, the gene expression analysis of stem cell, epithelial cell, and specific genes involved in TGF-β signalling were identified during the differentiation process using Two-step RT-PCR. Apart from that, protein expression analysis of epithelial markers was also determined using flow cytometer on day 1 and 21. Based on MTT assay, 0.3125, 0.625, and 1.25 ng/ml TGF-β1 and 0.156, 0.3125, and 0.625 μM ALK-5 inhibitor showed less cytotoxicity effects (more than 50%) and were selected for proliferation assay. The shortest PDT was represented by 1.25 ng/ml TGF-β1 (75 hours) and 0.625 μM ALK-5 inhibitor (68 hours) and these concentrations including cells in KGM only, showed there were cell morphological changes compared to control. The gene expression profile showed an absence of epithelial markers E-cadherin, ΔNp63, and Keratin5 for gene, and E-cadherin and pancytokeratin for protein expression indicated that the culture conditions unable to induce the differentiation process into epithelial-like cells. However, the presence of stem cell markers (NANOG, nestin, Rex1, and vimentin) and specific molecules involved in TGF-β signalling (TGFβR1, TGFβ1, Smad3, and Smad4) indicated that the cell culture in three different condition induced epithelial to mesenchymal transition (EMT) since the presence of TGFβ1 and Smad3 in TGF-β signalling that have been associated with EMT. Thus, KGM was unable to fully differentiate SHED into epithelial-like cells and hence, SHED were incapable to undergo mesenchymal to epithelial transition (MET).